Allergic reactions to COVID-19 vaccines: statement of the Belgian Society for Allergy and Clinical Immunology (BelSACI). Issue 3 (4th May 2022) - Tuyls, Sebastiaan; Van Der Brempt, Xavier; Faber, Margaretha; Gadisseur, Romy; Dezfoulian, Bita; Schrijvers, Rik; Froidure, Antoine
ABSTRACT: Vaccination against COVID-19 constitutes a huge hope and a major challenge. For the first time in modern history, a global vaccination campaign has started worldwide in a short period of time and with products that were recently developed. Consequently, legitimate concerns regarding the safety and tolerability of COVID-19 vaccines arise. In line with international allergy societies, the Belgian Society for Allergy and Clinical Immunology (BelSACI) provides this statement to guide health care providers (general practitioners, specialists including allergists) and stakeholders. In this statement, we first review current evidence on allergic reactions to vaccines and the potential risk factors that have been identified. Second, we provide a risk stratification method that may be used as a worksheet during the vaccination campaign. Finally, we discuss the management of suspected or confirmed allergic reactions following vaccination.